The Development of Information Systems for Poor Population Data - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen4, Quyen Le Hoang; Bich Huynh, Vy Dang; Andini, Yuli (Opción, 2019)
The poor population is the main problem for an area, so a good collection of poor population is something that must be done. Information system is one of the effective ways in term of data collection for poor population. The existence of an information system will certainly provide accurate data, so the policies taken by local governments are in accordance with the needs of their communities. Data collection of the poor population can also determine the direction of policy for local government in term of programs to reduce poverty. This research aimed to design a computerized data collection sys- tem for the poor population. The method used in making information system for the poor population was the System Development Life Cycle (SDLC).Stages started with system planning, system analysis, system design, im- plementation and maintenance. This information system was built using the Microsoft Visual Basic 6.0 programming.